Wind, solar and biogas power generation in water-stressed areas of Morocco considering water and biomass availability constraints and carbon emission limits - Mahdavi, Meisam [UNESP]; Awaafo, Augustine; Jurado, Francisco; Vera, David; Verdú Ramos, Ricardo Alan [UNESP] (Elsevier, 2023)
The energy sector of Morocco relies mainly on imported fossil fuels. The expensive import bills associated with fossils, as well as the global drive for greenhouse gas (GHG) emission reduction, have compelled the country to consider the utilization of renewable energy resources such as hydro, wind, and solar for energy generation. Power generation from wind and solar is highly intermittent hence require storage systems to guarantee supply security. Considering the abundant nature of sheep rearing in Morocco, power generation from sheep dung through anaerobic digestion (AD) can serve as an alternative power generation source to alleviate the intermittent situations of wind and solar since biomass supply for AD is not affected by the weather. Therefore, this paper evaluates the capability of hybrid power generation, using AD of sheep dung, wind, and solar in two selected areas of the Fez-Meknes region in Morocco. A mixed-integer linear programming model was implemented in A Mathematical Programming Language (AMPL) using a linear solver of CPLEX. The results of the analysis indicated that only standalone wind generation and hybrid wind/PV/biogas generation are able to meet the total load demand of the two study locations. The hybrid generation resulted in a total carbon emission of 349.30 and 3871.60 g/year at a cost of 13,088.38 and 145,394.13 $/year for Tazouta and Fez respectively in supplying the whole load of the study locations, whiles the standalone wind generator resulted in a total carbon emission of 274 and 2603 g/year at a total cost of 23,352 and 239,500 $/year for satisfying the electric load of these two regions respectively. The results shows that, hybrid solar/wind/PV is the most ideal for supplying power to the two study locations in terms of cost and load satisfaction, while the wind is the most ideal in terms of load satisfaction and carbon emissions.
Keywords: Biogas energy; Fez-Meknes rural areas; Photovoltaic electricity; Wind turbines